PATTERNS OF CARDIOMYOPATHY PROGRESSION IN TYPE 2 DIABETIC PATIENTS FROM HIGH-TEMPERATURE REGIONS - Xodjieva G.S. (Modern American Journals, 2025)
Cardiomyopathy in patients with type 2 diabetes mellitus (T2DM) is a major contributor to cardiovascular morbidity and mortality. This study investigates the clinical and pathophysiological features of cardiomyopathy progression in T2DM patients living in hot climatic conditions. Environmental stressors such as chronic heat exposure, dehydration, and altered circadian rhythms may exacerbate cardiac dysfunction and accelerate disease progression. The study analyzes a cohort of diabetic patients from the Bukhara region, assessing biochemical, echocardiographic, and clinical parameters over a 12-month period. Results suggest that elevated ambient temperatures correlate with increased myocardial stiffness, diastolic dysfunction, and autonomic imbalance. The findings underscore the need for region-specific guidelines in managing cardiovascular complications in diabetic patients.
Keywords: Type 2 diabetes mellitus, cardiomyopathy, hot climate, diastolic dysfunction, myocardial remodeling, environmental stress